Basal ganglia dysplasia and mTORopathy: A potential cause of postoperative seizures in focal cortical dysplasia. Issue 1 (19th December 2022) - Lee, Wei Shern; Macdonald‐Laurs, Emma; Stephenson, Sarah E M; D'Arcy, Colleen; MacGregor, Duncan; Leventer, Richard J; Maixner, Wirginia; Harvey, A Simon; Lockhart, Paul J
Abstract: Pathogenic somatic MTOR variants in the cerebral cortex are a frequent cause of focal cortical dysplasia (FCD). We describe a child with drug and surgery‐resistant focal epilepsy due to FCD type II who developed progressive enlargement and T2 signal hyperintensity in the ipsilateral caudate and lentiform nuclei. Histopathology of caudate nucleus biopsies showed dysmorphic neurons, similar to those in resected cortex. Genetic analysis of frontal and temporal cortex and caudate nucleus identified a pathogenic somatic MTOR variant [NM_004958.4:c.4375G > C (p.Ala1459Pro)] that was not present in blood‐derived gDNA. The mean variant allele frequency ranged from 0.4% to 3.2% in cerebral cortex and up to 5.4% in the caudate nucleus. The basal ganglia abnormalities suggest more widespread, potentially hemispheric dysplasia in this patient, consistent with the pathogenic variant occurring in early cerebral development. This finding provides a potential explanation for persistent seizures in some patients with seemingly complete resection of FCD or disconnection of a dysplastic hemisphere.